Sustainable Environmental Development: The Moderating Role of Environmental Identity. Issue 4 (October 2016) - Li, Dong‐xin; Kim, Sally; Lee, Yong‐Ki; Griffin, Mitch
Abstract : This study develops and tests a model of Chinese residents' evaluation of government developmental activities based on identity theory and social exchange theory. The study proposes hypotheses regarding the influences of perceived benefits and environmental identity on residents' satisfaction with the government, the moderating role of environmental identity in the relationship between perceived benefits and satisfaction, and the effect of satisfaction on residents' support intentions. The model is tested with data collected from 474 residents of four cities in China. Results show environmental identity, along with perceived economic and environmental benefits, plays a very important role in residents' satisfaction with the government. The significant moderating role of environmental identity suggests differential effects of perceived benefits on satisfaction are observed based on the level of environmental identity. Satisfaction is found to be important for obtaining residents' support for the government and future environmental development. Implications of the study are discussed.